2013
DOI: 10.5539/jas.v5n8p132
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Environmental Damage to Marine Protected Area: A Case of Perhentian Marine Park in Malaysia

Abstract: The Perhentian Island located in the East coast of Peninsular Malaysia is well-known for its rich coral reef ecosystems. Marine resources of Malaysia have been overexploited due to overfishing and tourism activities. As such no-take marine protected area (MPAs) were established in Malaysia, including Perhentian Island Marine Park to enable overexploited marine resources to recover and to conserve coral reef ecosystems. This paper examines the current level of activities causing damage to coral reef habitats in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…PPMP receives up to 90,150 tourists annually. The number of tourists is almost double from 2004 to 2011 ( Figure 2 Source: Islam et al (2013) www.gjournals.org 31…”
Section: Study Areamentioning
confidence: 99%
“…PPMP receives up to 90,150 tourists annually. The number of tourists is almost double from 2004 to 2011 ( Figure 2 Source: Islam et al (2013) www.gjournals.org 31…”
Section: Study Areamentioning
confidence: 99%
“…The islands are blessed with rich and diverse species of coral reefs with about 127 types of fishes. During the peak season from July to October, it is believed that the hotels and chalets in the islands especially Perhentian Kecil have 100% occupancy rate [39][40][41]. Data obtained from the Marine Park Department of Malaysia showed that the number of tourists to Perhentian Island in 2012 is 36,976 domestic and 66,529 foreign visitors.…”
Section: Methodsmentioning
confidence: 99%
“…The government has undertaken legal protection in order to protect coral reefs from fishing in the MPA areas, including Perhentian Island But legal protection has become less effective due to massive infrastructural development, as there are about 45 resorts/chalets, 19 dive shops, 40 souvenir shops, several restaurants and tea stalls employing a good number of local residents in Perhentian besar and Perhentian kecil. For the small area of Perhentian Island, the number of infrastructures was relatively high compared to other marine parks in the east coast of Peninsular Malaysia (Islam et al, 2013). The other reason for not taking proper care of Perhentian is the conflict of jurisdiction between the Federal government and the State government.…”
Section: Fisheries Management and Marine Protected Areasmentioning
confidence: 99%
“…In 2004, the responsibility of Marine Park management was transferred from Department of Forest Management to the Marine Parks Department Malaysia (MPDM) under the Ministry of Natural Resources and Environment (MNRE). The main reason for this arrangement was to promote sustainable resource management and enhance tourism in the marine parks (Islam et al, 2013). The Department of Forest Management and the MPDM fall under the Federal government's jurisdiction, while the land in the island belongs to the State Government, which decides on all land based development activities.…”
Section: Fisheries Management and Marine Protected Areasmentioning
confidence: 99%
See 1 more Smart Citation